2011
DOI: 10.1002/stem.665
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell‐Mediated Delivery of the Sodium Iodide Symporter Supports Radionuclide Imaging and Treatment of Breast Cancer

Abstract: Mesenchymal Stem Cells (MSCs) migrate specifically to tumors in vivo, and coupled with their capacity to bypass immune surveillance, are attractive vehicles for tumor-targeted delivery of therapeutic agents. This study aimed to introduce MSC-mediated expression of the sodium iodide symporter (NIS) for imaging and therapy of breast cancer. Tumor bearing animals received an intravenous or intratumoral injection of NIS expressing MSCs (MSC-NIS), followed by 99mTcO4- imaging 3-14Days (D) later using a BazookaSPECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 48 publications
0
74
2
Order By: Relevance
“…Nine out of 32 studies, with heterogeneous study design, met the predefined inclusion criteria and all were reviewed Of these, six studies were phase I (Dwyer et al, 2007;Woodward et al, 2007;Vlashi et al, 2009;Grisendi et al, 2010;Dwyer et al, 2011;Milane et al, 2011)and three were phase II clinical trials (Table 1) (Ueno et al, 2009;Resetkova et al, 2010;Viens et al, 2010). There was no published paper regarding phase III clinical trial on stem cell targeted therapy of breast cancer within the period of this study.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine out of 32 studies, with heterogeneous study design, met the predefined inclusion criteria and all were reviewed Of these, six studies were phase I (Dwyer et al, 2007;Woodward et al, 2007;Vlashi et al, 2009;Grisendi et al, 2010;Dwyer et al, 2011;Milane et al, 2011)and three were phase II clinical trials (Table 1) (Ueno et al, 2009;Resetkova et al, 2010;Viens et al, 2010). There was no published paper regarding phase III clinical trial on stem cell targeted therapy of breast cancer within the period of this study.…”
Section: Search Resultsmentioning
confidence: 99%
“…Moreover, in a recent study Dwyer et al (2011) showed that MSC-mediated expression of the sodium iodide symporter (NIS) is potentially is appropriate for imaging, tracking and therapy of breast cancer. By injection of MSC-NIS, human NIS (hNIS) gene expression in various tumor sites occurred and a significant reduction of tumor growth was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that MSCs are actively recruited to growing tumour stroma (Conrad et al 2007, Zischek et al 2009, Knoop et al 2011, Knoop et al 2013) mediated by high local concentrations of inflammatory chemokines and growth factors (Ponte et al 2007, Spaeth et al 2008, Kholodenko et al 2013. This tumour tropism constitutes the basis for the 'Trojan horse' approach, in which MSCs are used as shuttle vectors to deliver therapeutic agents into growing tumours , Dwyer et al 2011, Dembinski et al 2013, Zhu et al 2014, Zhang et al 2015, as we have successfully demonstrated in our previous work using the sodium iodide symporter (NIS) (Knoop et al 2011, Knoop et al 2013 and herpes simplex virus type 1 thymidine kinase (HSV-TK) (Zischek et al 2009 as therapy genes in various tumour models.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, types of stem cells, and especially mesenchymal stem cells (MSCs), that have been evaluated in several tumor models including breast, prostate, and ovarian cancer are used (11,15,23). However, the data are not adequate and some are contradictory to each other.…”
mentioning
confidence: 99%